Keselamatan produk dan perlindungan pengguna – satu tinjauan - Rahmah Ismail (Fakulti Undang - Undang, 2000)

(untitled)
Consumer are active participants in the market place. Without consumers market cannot function as it is now. As active participants and due to some weaknesses possessed by consumers, they have been given certain basic rights in order to ensure that they are not manipulated by manufacturers. One of those rights it right to safety in relation to products and services. Product safety is paramount important to consumer safety and should become a vital component of consumer protection legislation. This is because consumers are being exposed to various types of products which some of them are manufactured and presented in a sophisticated manner that really challenge the ability of the consumers to make a safe choice. Without proper guidance and protection, consumers are not able to identify and even to protect themselves against risks when using the products. Consumers need protection against unsafe products. Therefore, product safety law can serve as a protecting tool to ensure that consumers are presented only with safe products